The Effects of Divided Attention on Speech Motor, Verbal Fluency, and Manual Task Performance. - Dromey, Christopher; Shim, Erin (Journal of Speech, Language & Hearing Research, 2008)
Purpose: The goal of this study was to evaluate aspects of the functional distance hypothesis, which predicts that tasks regulated by brain networks in closer anatomic proximity will interfere more with each other than tasks controlled by spatially distant regions. Speech, verbal fluency, and manual motor tasks were examined to ascertain whether right-handed activity would interfere more with speech and language performance because of the presumed greater demands on the left hemisphere. Method: Twenty young adults completed a speech task (repeating a sentence), a verbal fluency task (listing words beginning with the same letter), and right- and left-handed motor tasks (placing pegs and washers in a pegboard) in isolation and concurrently. Results: Speech kinematic data showed that during concurrent performance of manual tasks, lip displacement and peak velocity decreased, whereas sound pressure level increased. Spatiotemporal variability increased when the nondominant hand was used for a motor task. Manual motor scores significantly decreased when concurrently performed with the verbal fluency task but not with sentence repetition. Conclusion: These findings suggest that the control of concurrent tasks may be more complex than is predicted by the functional distance hypothesis. Reprinted by permission of the publisher.